FORUM JUAL BELI FACEBOOK DAN FACEBOOK MARKETPLACE SOLUSI PEMASARAN PRODUK PERIKANAN - Arief Adhy Kurniawan; Prayoga Pribadi; Fadli Abdillah Subhi; Habib Al Ghazali (Yayasan Nusantara Hasana Berdikari, 2023)
This community service activity is carried out in Karangnangka Village, Kedungbanteng District, Banyumas Regency. The problem is that fish breeders, if they have problems with the marketing of the narrow area, sell themselves, so they have to go through collectors to make sales. Selling through middlemen is fast, but the price is lower. Therefore it is necessary to have a marketing medium so that fish breeders can sell their own fish in a larger area and at a higher price. The solution is with media marketing with Facebook Marketplace. The benefit received by fish breeders is that they can sell directly to consumers in a wider marketing area at a higher price than the price at the collector merchant level. In addition to farmers, fish breeders also have data customers that can be used at any time to offer their fish.